Anti-freezing hydrogel and application thereof in preparation of rapid bleeding stopping product for trauma
Through the amide reaction of dopamine-nanocellulose-polyvinyl alcohol composite anti-freeze hydrogel and the glycerol binary solvent system, the problem of hydrogel being easily frozen and poorly adhered at low temperatures is solved, and high efficiency is achieved antifreeze and hemostatic effects.
Patent Information
- Application Number
- CN202411600751.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing hydrogels are prone to freezing at low temperatures and have poor adhesion, which limits their application in special environments, especially in acute bleeding wounds.
Dopamine-nanocellulose-polyvinyl alcohol composite anti-freeze hydrogel is used to form a new polymer through amide reaction, and the anti-freeze performance is enhanced by using a binary solvent system of glycerol and water, while loading pro-coagulant drugs To improve hemostatic effect.
It achieves excellent tissue adhesion, frost resistance and rapid hemostasis effect of hydrogel, is suitable for high altitude and low temperature areas, and shows better hemostasis effect in acute trauma.
Smart Images

Figure CN119386247A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antifreeze hydrogels, and in particular relates to an antifreeze hydrogel and application thereof in preparing a rapid hemostasis product for trauma. Background Art
[0002] Dopamine (DA), also known as 4-(2-ethylamino)benzene-1,2-diol, can be polymerized on the surface of the material to form a polydopamine (PDA) nanofilm containing catechol units. This PDA has super strong tissue adhesion and good biocompatibility. In 2017, a research team from Southwest Jiaotong University in my country proposed a glycerol-hydrogel with PDA-modified carbon nanotubes (CNTs) as conductive nanofillers. The hydrogel has antifreeze and heat resistance, long-term stability, good conductivity, super strong mechanical properties and tissue adhesion. Polyvinyl alcohol (PVA) is a widely used biomedical polymer material, but its mechanical properties are weak and it lacks effective mechanical protection for wounds. In 2020, Feng Jiang's team at the University of British Columbia in Canada reported on research on the preparation of a new conductive hydrogel using PVA and cellulose nanofibers (CNFs). The team prepared PVA-CNF organic hydrogel by a one-pot sol-gel synthesis method using PVA and TEMPO-oxidized CNF, and used the DMSO / H2O binary solvent system to suppress the freezing point of water molecules, enhancing the mechanical properties and conductivity of the hydrogel while giving it good antifreeze properties. In 2018, the Institute of Physical and Chemical Engineering of the Chinese Academy of Sciences disclosed a self-healing hydrogel of cellulose-dopamine-polymer composite material and its preparation method and application invention patent (application publication number: CN108359056A). In addition, glycerol (glycerol) mixed with water to form a binary solvent, replacing the single water solvent in traditional hydrogels, can significantly improve the antifreeze performance of the hydrogel, and the lowest freezing point (-46.5°C) is reached when the mass concentration of glycerol reaches 66.7%.
[0003] In recent years, hydrogels have received extensive attention in the biomedical field, but the fact that hydrogels are easy to freeze at low temperatures and have poor adhesion limits their application in special environments. PDA-CNTs hydrogels have the potential to be used as wound dressings for frostbite and burns, but they are not very effective for acute bleeding wounds that are more common in clinical practice, and their scope of application is limited. As a conductive material, PVA-CNF hydrogels have strong mechanical properties but almost no tissue adhesion and cannot be used directly as wound dressings. The invention patent (CN108359056A) aims to prepare conductive materials that have repair capabilities and can be recycled. There are no reports on the application of biomedical materials, and the hydrogels do not have antifreeze properties. Summary of the invention
[0004] In view of the above technical problems, the object of the present invention is to provide an antifreeze hydrogel and its application in the preparation of a rapid hemostasis product for trauma, so as to solve the above technical problems.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel, which is prepared by the following steps:
[0007] 1) preparing a nanocellulose solution;
[0008] 2) adding a catalyst, a cross-linking agent and dopamine to the nanocellulose solution, reacting at 75° C. to 80° C. in a nitrogen environment for 20 h to 24 h to obtain a first mixed solution; the mass ratio of the nanocellulose, dopamine, catalyst and cross-linking agent is 1:0.9 to 1:0.5 to 0.6:0.9 to 1;
[0009] 3) cooling the first mixed solution, dialyzing it, and drying it to obtain an intermediate solid product;
[0010] 4) mixing the intermediate solid product with water to obtain a second mixed solution, then adding glycerol and polyvinyl alcohol, and after the intermediate solid product is completely dissolved, adding borax solution to obtain a third mixed solution; the mass volume ratio of the intermediate solid product, water, glycerol, polyvinyl alcohol and borax solution is 0.1g-0.3g:3ml-5ml:10ml-12ml:0.3g-0.4g:3ml-5ml;
[0011] 5) adding a procoagulant drug to the third mixed solution to obtain a fourth mixed solution, reacting the solution at 90° C. to 92° C. for 0.5 h to 1 h, and then cooling the solution to room temperature to form a dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel; the mass ratio of the procoagulant drug to the intermediate solid product is 3 to 4:10.
[0012] The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel material of the present invention comprises nanocellulose, dopamine, a catalyst and a cross-linking agent in a mass ratio of 1:0.9-1:0.5-0.6:0.9-1 for mixed reaction, and a part of the nanocellulose containing carboxyl groups is combined with dopamine through an amide reaction to form a new high molecular polymer (i.e., the intermediate solid product). The intermediate solid product, water, glycerol, polyvinyl alcohol and borax solution are mixed for reaction in a mass volume ratio of 0.1g-0.3g:3ml-5ml:10ml-12ml:0.3g-0.4g:3ml-5ml. The intermediate solid product is combined with polyvinyl alcohol to form a hydrogel. The glycerol and water are mixed to form a binary solvent, so that the antifreeze performance of the hydrogel is enhanced, and the hydrogel can better adapt to extreme environmental conditions such as high cold. Furthermore, a common procoagulant drug in clinical treatment is loaded on the hydrogel in a mass ratio of 3-4:10 to the intermediate solid product. The hemostatic effect thereof is more advantageous than that of ordinary wound dressings.
[0013] Furthermore, in step 1), the nanocellulose solution is prepared as follows:
[0014] Nanocellulose is added into water and stirred to dissolve at room temperature to obtain a uniformly dispersed nanocellulose solution.
[0015] Furthermore, the mass ratio of the nanocellulose to water is 1:99-500.
[0016] Furthermore, the nanocellulose is selected from carboxymethyl cellulose and nanocellulose oxidized with 2,2,6,6-tetramethylpiperidinium N-oxide.
[0017] Furthermore, in step 2), the catalyst is N-hydroxysuccinimide, and the cross-linking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride.
[0018] Furthermore, in step 4), the mass percentage concentration of the borax solution is 0.5% to 4%.
[0019] Furthermore, in step 5), the procoagulant drug is selected from one of ethylphenolsulfonamide, carbachol and aminobenzoic acid or any combination thereof.
[0020] In a specific embodiment of the present invention, the procoagulant drug used is ethylphensulfonamide powder, CAS number: 2624-44-4, ethylphensulfonamide is an internal hemostatic drug, but when used externally, the hemostatic effect is very small. The present invention uses hydrogel to load ethylphensulfonamide to achieve significant effects in trauma hemostasis, expanding the application range of ethylphensulfonamide.
[0021] Furthermore, in step 5), the molding is performed by placing the fourth mixed solution in a mold, and the thickness of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel is 0.5 cm-1 cm.
[0022] In a second aspect, the present invention provides the use of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel in the preparation of a rapid hemostasis product for trauma.
[0023] In a third aspect, the present invention provides the use of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel in the preparation of skin damage repair products.
[0024] The present invention has the following beneficial effects:
[0025] The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel of the present invention has excellent tissue adhesion, antifreeze and rapid hemostatic effects, and can be used alone without relying on other adhesive substances; it is applicable in high-altitude and low-temperature areas; it is applicable when facing wounds of different shapes; in the case of acute trauma, the wound bleeds over a large area, and the hydrogel-loaded drug will directly contact the blood after release, which is very similar to the principle of intravenous drip usage to exert the drug effect, with high local concentration and more advantageous hemostatic effect than ordinary wound dressings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the Fourier transform infrared (FT-IR) spectrum of the hydrogel of the present invention.
[0027] Figure 2 The figure is the thermogravimetric test result of the hydrogel of the present invention.
[0028] Figure 3 This is an electron microscope photograph of the hydrogel sample without glycerol after freeze drying.
[0029] Figure 4 This is the in vitro release curve of ethylphenolsulfonamide.
[0030] Figure 5 is the adhesion performance of the hydrogel, A is the morphology of the hydrogel, B is the adhesion between the hydrogel and latex gloves, C is the adhesion between the hydrogel and human skin, and D is the adhesion between the hydrogel and pig skin.
[0031] Figure 6 This is the wound healing curve of mouse skin. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0033] Glossary:
[0034] CNF: nanocellulose, purchased from Northern Century (Jiangsu) Cellulose Materials Co., Ltd., product number is 202407291003.
[0035] TEMPO: 2,2,6,6-tetramethylpiperidinium N-oxide.
[0036] NaBr: sodium bromide.
[0037] NaCIO: sodium hypochlorite.
[0038] NaOH: sodium hydroxide.
[0039] EDC: 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride.
[0040] NHS: N-hydroxysuccinimide.
[0041] PVA: polyvinyl alcohol.
[0042] CMC: carboxymethyl cellulose.
[0043] Example 1: Preparation of dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel
[0044] Disperse 1g CNF in 90mL water under ice water bath and mix by ultrasonic. Continue to add 10ml mixed solution of TEMPO (0.0156g) and NaBr (0.103g) fully dissolved in pure water, and add 10mL of 10% NaCIO solution. After adding NaOH and stirring the reaction for 2h under the condition of pH = 10.3-10.5, add 10ml of ethanol to quench the reaction. After centrifugation, the lower solid mixture is obtained, and 200ml of pure water is added to redissolve and dialyze (molecular weight cutoff is 70kDa) for 3 days. After freezing (temperature -40℃) and drying the dialyzed liquid, use pure water to prepare a nanocellulose solution with a mass fraction of 1%.
[0045] Under an oil bath, add the above nanocellulose solution (50 ml) and EDC (0.48 g) to a beaker, and stir and dissolve at 80°C and 500 rpm for 1 h. Add 0.29 g NHS and 0.475 g DA to the dissolved solution, and adjust the pH value to 5.0 with dilute hydrochloric acid (concentration 0.1 mol / L). The prepared mixed solution is reacted at 500 rpm and 80°C for 24 h under N2 protection, and the solution is cooled to room temperature (20°C-24°C) to obtain a first mixed solution.
[0046] The first mixed solution was dialyzed with pure water (molecular weight cut-off of 70 KDa) for 5 days, the conductivity of the dialysate was measured every day and the dialysate was replaced with pure water for continuous dialysis, the conductivity of the dialysate measured on the 1st, 2nd, 3rd and 4th days was 51.6, 11.2, 1.8 and 1.8 Siemens / meter (S / m) respectively, and the conductivity of the dialysate did not change from the third day and was consistent with the conductivity of pure water under the same conditions, and the dialysis was completed. The above dialysate was dried at 60°C for 8h to obtain an intermediate solid product (0.46g).
[0047] Next, under an oil bath, the intermediate solid product (0.2 g) was added to pure water (4 ml) to obtain a second mixed solution, and then propylene glycol (12 ml) and PVA (0.4 g) were added, and the solution was observed to be completely dissolved after stirring at 130°C for 24 hours, and a 2% mass fraction of borax solution (4 ml) was added and the temperature was adjusted to 90°C to obtain a third mixed solution. Ethylphenolsulfonamide (75 mg) was added to the third mixed solution to obtain a fourth mixed solution, and stirring was continued for 0.5 hours, and then the solution was placed in a mold and cooled to room temperature (20°C-24°C), and a brown transparent hydrogel with a thickness of 0.5 cm was obtained, namely, dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel (hereinafter referred to as hydrogel).
[0048] Product performance evaluation:
[0049] In order to better evaluate the performance of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel of the present invention and further verify the synergistic effect between the functional components, the following verification was performed.
[0050] 1. Infrared spectrum detection
[0051] The infrared spectrum detection results of the intermediate solid product of Example 1 are as follows Figure 1 As shown. 1577cm -1 NH bending vibration was detected at , confirming that the amino groups in dopamine and the carboxyl groups of nanocellulose formed amide bonds through amide reaction (reference doi: 10.1016 / j.carbpol.2020.117188), thereby increasing the cross-linking degree of the hydrogel and helping to improve its mechanical strength and stability. In addition, the catechol groups in dopamine have adhesive properties, and the formation of amide bonds can enhance the adhesion between dopamine and nanocellulose, allowing the hydrogel to better fit the wound or tissue surface.
[0052] 2. Thermogravimetric analysis
[0053] The thermogravimetric analysis results of the hydrogel in Example 1 are as follows: Figure 2As shown. The hydrogel mainly lost weight at 108.852℃ and 253.388℃, with the weight loss percentages being 25.812% and 68.346% respectively. Considering the hydrogel composition and proportion, the weight loss of water and glycerol were considered respectively. The results suggest that the hydrogel has good thermal stability.
[0054] 3. Scanning electron microscopy analysis
[0055] The hydrogel of Example 1 (without glycerol and coagulation drugs) was photographed by scanning electron microscope (SEM) after freeze-drying. Figure 3 As shown, the structural characteristics of the hydrogel at the microscopic scale are demonstrated. The diversely arranged pore network is conducive to the drug loading of the hydrogel and maintains good water absorption performance and mechanical strength.
[0056] 4. Drug Release Analysis
[0057] 0.5 g of the hydrogel of Example 1 was placed in 20 ml of PBS solution, and an in vitro drug release experiment was performed at a centrifuge speed of 120 rpm. Samples were taken at 0.5, 5, 24, 48, and 72 hours to measure the drug concentration of ethylphenolsulfonamide in the solution. The results are shown in FIG. Figure 4 As shown, the drug is released rapidly in the early stage of drug release (0.5-24h), and is basically released completely in the late stage of drug release (after 24h), and the drug concentration in the solution remains stable.
[0058] 5. Skin Adhesion Test
[0059] The test results of the hydrogel obtained in Example 1 on the adhesion of the hydrogel to latex gloves, human skin and pig skin under experimental conditions are as follows: Figure 5 As shown, the results show that the hydrogel obtained in Example 1 has ideal adhesion to latex gloves, human skin and pig skin at room temperature, and can remain adhered without falling off easily when the skin morphology changes or the body moves.
[0060] 6. Antifreeze performance test
[0061] The antifreeze performance of the hydrogel obtained in Example 1 and the hydrogel obtained without adding glycerol in proportion was tested: the hydrogels were placed in 25°C, 4°C, and -20°C environments for 24 hours, and it was observed that the hydrogels in Example 1 were all in a colloidal state. At -20°C, the hydrogels in the glycerol-free group turned into a solid and lost their adhesion ability.
[0062] 7. Skin damage repair effect test:
[0063] The hydrogel obtained in Example 1 was subjected to a skin damage repair test, and the test method was as follows: (1) Establishment of a mouse skin defect wound model: C57BL / 6 male mice were anesthetized by intraperitoneal injection of 0.5% chloral hydrate solution, the hair on the back of the mice was removed with a depilatory cream, and the skin on the back of the mice was disinfected with a cotton ball containing 75% ethanol solution by volume. After the ethanol has completely evaporated, a round hole punch with a diameter of 0.6 cm is used to create a full-thickness skin defect wound on each side of the back, and the maximum diameter and minimum diameter are measured with a vernier caliper to estimate the initial wound area; (2) Drug administration: The hydrogel obtained in Example 1 is cut into pieces and placed in a 75% ethanol solution for disinfection for 30 minutes. After being irradiated under an ultraviolet lamp for 2 hours, it is washed with a PBS solution for 5 times. After the excess water on the surface of the hydrogel is absorbed with sterile filter paper, it is applied to the surface of the mouse skin wound and protected with sterile gauze and adhesive tape; (3) Mouse skin defect healing time detection: The mouse wound is regularly observed and measured, and the maximum and minimum diameters of the wound are measured with a vernier caliper, and the wound area is estimated to evaluate the wound healing.
[0064] Test results such as Figure 6 As shown in Table 1, the hydrogel provided by the present invention has an excellent skin damage repair effect. The hydrogel obtained in Example 1 is used as experimental group 1, the hydrogel without ethylphenolsulfonamide is used as experimental group 2, the wound is smeared with a PBS solution containing 3 mg / ml ethylphenolsulfonamide and then covered with sterile gauze as experimental group 3, and the wound is covered with simple sterile gauze as a control group. By comparing the hydrogel obtained in Example 1 with the other groups, it can be found that the present invention improves the skin damage repair speed of the hydrogel by adding a hemostatic drug to the hydrogel.
[0065] Table 1 Results of two-way ANOVA
[0066]
[0067] Note: ***, ** represent 1% and 5% significance levels respectively.
[0068] VII. Test on hemostasis effect of tail-cut bleeding in mice
[0069] The hydrogel obtained in Example 1 was used to test the hemostatic effect of tail amputation in mice, and the test method was as follows: (1) Establishment of tail amputation bleeding model in mice: C57BL / 6 male mice were anesthetized by intraperitoneal injection of 0.5% chloral hydrate solution by mass fraction, and the 1 / 2 area at the end of the mouse tail was disinfected with a cotton ball with a volume fraction of 75% ethanol solution. After the ethanol was completely evaporated, the mouse was fixed and the tail was cut at the end of the mouse tail with sterilized scissors at 1 / 3 of the tail. There was obvious bleeding at the end of the tail, and the starting time of bleeding was recorded; (2) Drug treatment: After covering the wound with the hydrogel obtained in Example 1 for 20 seconds, the bleeding of the mouse tail was observed with sterile filter paper, the hemostasis time was recorded, and the group was compared with the group without hemostatic drug hydrogel; (3) The bleeding time of the tail of each group of mice was calculated and statistical analysis was performed. The test results are shown in Table 2:
[0070] Table 2 Independent sample T test analysis results
[0071]
[0072]
[0073] Note: ***, ** represent 1% and 5% significance levels respectively, / means the item is not included.
[0074] 8. Testing the hemostatic effect in the mouse liver bleeding model
[0075] The brown transparent hydrogel obtained in Example 1 was used to test the hemostatic effect of the mouse liver bleeding model, and the test method was as follows: (1) Establishment of mouse liver bleeding model: C57BL / 6 male mice were anesthetized by intraperitoneal injection of 0.5% chloral hydrate solution by mass fraction, and the chest and abdominal skin areas of the mice were disinfected with cotton balls with a volume fraction of 75% ethanol solution. After the ethanol was completely volatilized, the mouse was fixed and the chest and abdominal areas were dissected to expose the mouse liver. While retaining the blood vessels, the mouse liver was carefully placed on sterile filter paper, the serous fluid around the liver was carefully removed, and the liver was punctured at the midpoint of the lower end of the front edge of the liver with a 16G sterile syringe needle to induce liver bleeding, and the starting time of bleeding was recorded; (2) Drug administration: The wound was covered with the hydrogel obtained in Example 1, and the liver bleeding was observed using sterile filter paper, the hemostasis time was recorded, and the group was compared with the group without hemostatic drug hydrogel; (3) The duration of liver bleeding in each group of mice was calculated, the amount of bleeding was measured by measuring the pre-weighed sterile filter paper, and statistical analysis was performed respectively. The test results are as follows:
[0076] Table 3 Independent sample T test analysis results
[0077]
[0078] Note: ***, ** represent 1% and 5% significance levels respectively, / means the item is not included.
[0079] The above data show that the hydrogel provided by the present invention has an excellent hemostatic effect. By comparing the hydrogel provided in Example 1 with the hydrogel without hemostatic drugs, the present invention improves the hemostatic effect of the hydrogel by adding hemostatic drugs into the hydrogel.
[0080] It should be noted that when the claims of the present invention involve numerical ranges, it should be understood that the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. In order to avoid redundancy, the present invention describes a preferred embodiment.
[0081] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel, characterized in that: Prepared by the following steps: 1) preparing a nanocellulose solution; 2) adding a catalyst, a cross-linking agent and dopamine to the nanocellulose solution, reacting at 75° C. to 80° C. in a nitrogen environment for 20 h to 24 h to obtain a first mixed solution; the mass ratio of the nanocellulose, dopamine, catalyst and cross-linking agent is 1:0.9 to 1:0.5 to 0.6:0.9 to 1; 3) cooling the first mixed solution, dialyzing it, and drying it to obtain an intermediate solid product; 4) mixing the intermediate solid product with water to obtain a second mixed solution, then adding glycerol and polyvinyl alcohol, and after the intermediate solid product is completely dissolved, adding borax solution to obtain a third mixed solution; the mass volume ratio of the intermediate solid product, water, glycerol, polyvinyl alcohol and borax solution is 0.1g-0.3g:3ml-5ml:10ml-12ml:0.3g-0.4g:3ml-5ml; 5) adding a procoagulant drug to the third mixed solution to obtain a fourth mixed solution, reacting the solution at 90° C. to 92° C. for 0.5 h to 1 h, and then cooling the solution to room temperature to form a dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel; the mass ratio of the procoagulant drug to the intermediate solid product is 3 to 4:
10.
2. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 1, characterized in that: In step 1), the nanocellulose solution is prepared as follows: Nanocellulose is added into water and stirred to dissolve at room temperature to obtain a uniformly dispersed nanocellulose solution.
3. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 2, characterized in that: The mass ratio of the nanocellulose to water is 1:99-500.
4. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 3, characterized in that: The nanocellulose is selected from carboxymethyl cellulose and nanocellulose oxidized by 2,2,6,6-tetramethylpiperidinium N-oxide.
5. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 4, characterized in that: In step 2), the catalyst is N-hydroxysuccinimide, and the cross-linking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride.
6. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 5, characterized in that: In step 4), the mass percentage concentration of the borax solution is 0.5% to 4%.
7. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 6, characterized in that: In step 5), the procoagulant drug is selected from one of ethylphenolsulfonamide, carbachol and aminobenzoic acid or any combination thereof.
8. The dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to claim 7, characterized in that: In step 5), the fourth mixed solution is placed in a mold for molding, and the thickness of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel is 0.5 cm-1 cm.
9. Use of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to any one of claims 1 to 8 in the preparation of a rapid hemostasis product for trauma.
10. Use of the dopamine-nanocellulose-polyvinyl alcohol composite antifreeze hydrogel according to any one of claims 1 to 8 in the preparation of skin damage repair products.
Citation Information
Patent Citations
Polymer composite material with hemostasis and anti-adhesion properties and preparation method and application thereof
CN104922740A
Self-healing hydrogel of cellulose-dopamine-polymer composite material as well as preparation method and application of self-healing hydrogel
CN108359056A
Preparation method of high-toughness antifreeze / heat resistant / antibacterial plant polyphenol nanocellulose conductive hydrogel
CN109651624A
Polyacrylamide-nanocellulose crystal-silver nanoparticle composite conductive anti-freezing organic hydrogel as well as preparation method and application thereof
CN113248730A
Self-healing anti-freezing conductive fibroin hydrogel and preparation method thereof
CN114409926A